Asbab Al-Nuzul Surat Al-Baqarah Ayat 142 dan 144 (Kajian Analisis Historis tentang Perpindahan Kiblat) - Lady Eka Rahmawati (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
This study explains the interpretation of the commentators in Surah al-Baqarah verses 142 and 144. In the explanation, it states in detail the meaning of lafaz, asbab al-Nuzul verse, the meaning of the verse globally, and understanding of the verse and the content of the verse. The important point in this study is the linkage of the narrations that become the asbab of al-Nuzul verse in revealing the content and meaning of the verse comprehensively. Surah al-Baqarah verses 142 and 144 explain the history of the Qibla movement. This verse is clear evidence of the existence of nasakh and mansukh verses in the Qur'an. So it is known that the first Nasakh verse contained in Islamic Shari'ah is a verse about the Qibla movement.